Dynamic testing of full-size rocket aerosol generators utilized for impacting on atmospheric processes - Zasaviţchi, Efim (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2014)
On the basis of an ingenious technique developed for dynamic testing of full-size generators of crystallizing aerosols used for impacting on cloud processes, the dependences of the yield of the pyrotechnic compositions of generators of "Alazan-6" and "Loza-2" rockets on the year of their production have been studied. Results of the examination of the activation rate of pyrotechnic compositions of the different anti-hail rockets ("Alazan-6" and "Loza-2") have been described. It has been shown that the pyrotechnic compositions of "Loza-2" anti-hail rockets exhibit a relatively higher activation rate than the pyrotechnic composition of "Alazan-6" rockets..